2009
DOI: 10.1007/s00232-009-9213-1
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Membrane Fluidity in the Etiology of Multiple Sclerosis

Abstract: Organisms adjust the order, or fluidity, of their cellular membranes in response to changes in their physiochemical environment by adjusting the lipid composition of their membranes. We investigated membrane fluidity using the phospholipid, fatty acid and cholesterol content of red blood cells (RBCs) from multiple sclerosis (MS) patients and correlated this with C-reactive protein (CRP) as well as with the severity of neurological outcome as measured by the Kurtzke Expanded Disability Status Scale (EDSS) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…Monolayer molecular species composition also affects physical properties. Organisms can adjust the order or fluidity of their cellular membranes in response to changes in their physiological environment by altering their lipid composition [50]. Alterations in brain and blood phospholipid composition consistent with an adjustment in the order or fluidity of the membrane in these tissues in response to PPA infusions were observed in this study.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Monolayer molecular species composition also affects physical properties. Organisms can adjust the order or fluidity of their cellular membranes in response to changes in their physiological environment by altering their lipid composition [50]. Alterations in brain and blood phospholipid composition consistent with an adjustment in the order or fluidity of the membrane in these tissues in response to PPA infusions were observed in this study.…”
Section: Discussionsupporting
confidence: 56%
“…Phospholipids are the major structural components of neuronal and other cellular membranes, and include PC, PE, PS, PI, and SM [50,51]. All of these phospholipid classes were observed to have altered molecular species distribution following PPA infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of the different phospholipid molecules depend on their different head-groups as well as on the type of fatty acids they contain (Williams, 1998;Horrobin, 1999) and their composition in cell membranes determines the degree of fluidity of the membrane structures. Phospholipids from both red blood cell (Hon et al, 2009c) and peripheral blood mononuclear cell (Hon et al, 2011b) membranes have been reported in detail and specifically their function in determining cell membrane fluidity and their role in disease outcome in patients with multiple sclerosis.…”
Section: Membrane Phospholipidsmentioning
confidence: 99%
“…These observations were neglected until the past few years and no one questioned the influence of RBC fragility and free hemoglobin (Hb) in MS. But this has changed in recent years 26. In 2009, an impaired fluidity of RBC membranes in MS was reported 2.…”
Section: Introductionmentioning
confidence: 99%
“…But this has changed in recent years 26. In 2009, an impaired fluidity of RBC membranes in MS was reported 2. In 2011, circulating free Hb was shown to disrupt the blood–brain barrier, accompanied by iron deposition, lipid peroxidation, and perivascular inflammation 3.…”
Section: Introductionmentioning
confidence: 99%